Evaluation of push-out bond strength in fiberglass posts cemented in natural teeth using different cementation protocols - Gabriela Marina Falconí-Borja; Carla Grimaneza Molina-Pule; Byron Vinicio Velásquez-Ron; Ana del Carmen Armas-Vega (Universidad de Antioquia, 2016)
Introduction: the clinical success of adhesive systems is based on the use of a responsible for creating microporosity in the dental structure acid and arises assess in vitro the degree of microfiltration in direct restorations with cavities class V where two adhesive systems differently used composition and at different periods of time. Methods: in the cervical third of 60 third molars extracted by therapeutic indication performed by diamond instruments, two cavities one on the vestibular side and one on the palatal or lingual side; It separated into two groups of 30 in the first acid conditioning was performed and then applied -Voco Admire bond while the second group Futurabond-Voco applied; both groups were restored with resin composite Admira-Voco, each group was divided into two subgroups of 15 subgroups A were subjected to thermal cycling for 10800 cycles and 5400 cycles B subgroups. It concluded these periods proceeded to staining with methylene blue and then a cut is made lengthwise to assess the income of the dye in the interface formed; this pigmentation was evaluated and measured under stereomicroscope. Results: the obtained data were statistically analyzed by Tukey's test, which showed the existence of differences between the groups evaluated, so evident at the level of cervical margin with a p ˃ 0.05. Conclusion: it is evident that the artificial aging increased microfiltration resin composite restorations regardless of the type of adhesive system used.